More answers

Lvl 1

3

Q: What is 3 2x - 3 x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(2x + 3)(x + 1 ) = 2x^2 +5x +3

(2x + 1) (x + 3) = 2x2 + 7x + 3

2x2 + 7x + 3 = (2x + 1)(x + 3)If 2x2 + 7x + 3 = 0 then:(2x + 1)(x + 3) = 0⇒ (2x + 1) = 0 → x = -1/2or (x + 3) = 0 → x = - 3

if it is -X then X=5 if it was minus X the X=10

(2x + 3)(x + 1)

Related questions

(2x + 3)(x + 1 ) = 2x^2 +5x +3

x+3(x+1)=2x x + 3x + 3 = 2x 2x + 3 = 0 2x = -3 or x = -1.5

(2x + 1) (x + 3) = 2x2 + 7x + 3

2x2 + 7x + 3 = (2x + 1)(x + 3)If 2x2 + 7x + 3 = 0 then:(2x + 1)(x + 3) = 0⇒ (2x + 1) = 0 → x = -1/2or (x + 3) = 0 → x = - 3

2x + 3 = x + 1 Subtract x from both sides: x + 3 = 1 Subtract 3 from both sides: x = -2

x = 1 ------------- 3 = 2x + 1 -1 -1 2=2x /2 /2 1=x

Here,x+2x+3=? Now, X+2x=-3 Or,3x=-3 (1x+2x) Or,x=-3รท3 Or,x=-1 Therefore,X=-1

if it is -X then X=5 if it was minus X the X=10

(2x + 3)(x + 1)

(x + 3)(x - 1)

4

1